E-Course Design of Middle/MTs Teacher Training Using Google Classroom - Yuliani, Refi Elfira; Heru, Heru (International Journal of Elementary Education, 2021)
The ability to design online learning was a skill that teachers in integrating ICT in Learning must possess. The problems faced by teachers in implementing online learning were complex, starting from internet access to the use of applications/software that can be used in online learning. This study aimed to produce an e-course for teacher training for SMP/MTs using the open-source google classroom. This research used a development research method with media evaluation using formative Evaluation Tessmer. As developed in this study was a teacher training media using google classroom. The research subjects were junior high school and MTS teachers, with 28 people involved during the training process activities. The instrument used in this research was a questionnaire. The questionnaire was given to the experts, and the participants of the small group trial were questionnaires to assess the e-course google classroom. The questionnaire given to the field test participants was to see the potential effect of learning using e-courses on the teacher's TPACK ability. The data analysis method used was descriptive qualitative. Based on the research results that have been done, it can be concluded that the e-course teacher training using google classroom was categorized as valid and practical. Validity was obtained from the assessment of the material, media, and language experts and was one-to-one. Practicality was obtained from the results of the small group trial by analyzing the results of the questionnaire distributed to the small group trial participants so that the average percentage of teacher assessment through the questionnaire was 92.5%. E-course had a potential effect on teacher TPACK with an average rate of 82.46%, classified as good. Based on the results obtained, it can be concluded that the developed training e-course was valid, practical, and had a potential effect on the achievement of TPACK. That was, the e-course that has been designed was effective.